Cellular Toxicity Mechanisms and the Role of Autophagy in Pt(IV) Prodrug-Loaded Ultrasmall Iron Oxide Nanoparticles Used for Enhanced Drug Delivery - L. Gutiérrez-Romero; L. Rivas-García; C. Sánchez-González; J. Llopis; E. Blanco; M. Montes-Bayón (MDPI AG, 2021)
Ultrasmall iron oxide nanoparticles (<10 nm) were loaded with cis-diamminetetrachloroplatinum (IV), a cisplatin (II) prodrug, and used as an efficient nanodelivery system in cell models. To gain further insight into their behavior in ovarian cancer cells, the level of cellular incorporation as well as the platination of mitochondrial and nuclear DNA were measured using inductively coupled plasma mass spectrometry (ICP-MS) strategies. Quantitative Pt results revealed that after 24 h exposure to 20 µM Pt in the form of the Pt(IV)-loaded nanoparticles, approximately 10% of the incorporated Pt was associated with nuclear DNA. This concentration increased up to 60% when cells were left to stand in drug-free media for 3 h. These results indicated that the intracellular reducing conditions permitted the slow release of cisplatin (II) from the cisplatin (IV)-loaded nanoparticles. Similar results were obtained for the platination of mitochondrial DNA, which reached levels up to 17,400 ± 75 ng Pt/ mg DNA when cells were left in drug-free media for 3 h, proving that this organelle was also a target for the action of the released cisplatin (II). The time-dependent formation of Pt-DNA adducts could be correlated with the time-dependent decrease in cell viability. Such a decrease in cell viability was correlated with the induction of apoptosis as the main route of cell death. The formation of autophagosomes, although observed upon exposure in treated cells, does not seem to have played an important role as a means for cells to overcome nanoparticles' toxicity. Thus, the designed nanosystem demonstrated high cellular penetration and the "in situ" production of the intracellularly active cisplatin (II), which is able to induce cell death, in a sustained manner.